Análise da via auditiva em sujeitos normo-ouvintes com zumbido e de uma proposta de aconselhamento fonaudiológico - Bruno, Rúbia Soares (2018)
Objectives: To investigate the physiological functionality at different levels of the auditory pathway in normal-hearing subjects with chronic tinnitus and, secondly, to verify the outcome of a single counseling session in the reducing perception of tinnitus. Method: Cross-sectional, longitudinal and quantitative study. Subjects with auditory thresholds within normality patterns in all frequencies bilaterally, presenting(SG) or not(CG) chronic tinnitus, participated in the study. The research was divided into two stages. The first included anamnesis, Tinnitus Handicap Inventory(THI), Visual Analogue Scale(VAS), Acuphenometry, High-Frequency Audiometry(HFA), Transient Otoacoustic Emissions(TOAE), Brainstem Auditory Evoked Potential(BAEP) with click stimulus , Frequency Following Response(FFR-speech), and Long-Latency Auditory Evoked Potential(LLAEP). For the second,the SG was divided into two(SG Counseling and SG Music);for the first, it was conducted speech therapy counseling in a single session and for the second, it was oriented to listening to music(considered comparison group). After one month, a return was registered for a reapplication of VAS and THI. Results:Twenty-two subjects aged between 18 and 59 years-old, which were predominantly female participated. Regarding the characterization of the sample, there was predominance of the whistling type tinnitus and of continuous sensation, sudden perception and the constant and bilateral manifestation with a higher incidence in the left ear. The intensity was reported with variation. As improvement factors no aspect researched influenced the symptom. As worsening factors, prevailed the stress and the silent environment. Considering the behavioral aspects, most of the subjects did not report headache,neck,low back and thoracic pain nor complaint related to temporomandibular joint dysfunction. As for eating habits, there was an excess of consumption of chimarrão and sweets with long periods of fasting. Regarding emotional issues, anxiety predominated. In Acuphenometry there was the prevalence of acute pitch and loudness within the range suggested by the literature. For the HFA, the SG presented increased values in relation to the CG, but without statistically significant differences. In the TOAE, there was predominance of presence of responses in both groups. For BAEP, analyzing latencies and interpeak intervals, there were no statistically significant differences. In the FFR-speech there were no differences in the latency, amplitude, interpeak and slope analysis between the groups, but it was found the amplitude of the V wave greater for the CG. In the LLAEP, a greater occurrence of absences of the potentials P1,N2,P300 in the SG was found. For the second stage, the SG Counseling showed improvement and statistically significant differences before and after treatment compared to the SG Music. Conclusion: It was possible to investigate the physiological functionality in the different levels of the auditory pathway in normal-hearing subjects presenting chronic tinnitus. The findings did not show statistically significant differences in the TOAE in the SG;in contrast, the HFA demonstrated significant changes in peripheral auditory regions. The BAEP showed no differences between the groups, but in the LLAEP and FFR can be observed changes in the SG and also of non-auditory factors. Speech therapy counseling in a single session proved to be effective in reducing the perception of the symptom,being verified through VAS and THI.